Case Report: Dermatitis Kontak Iritan Pada Wanita 54 Tahun - Setiawan, Putri Ayundari; Graharti, Risti; Fatmasari, Dina (CV. Jasa Sukses Abadi, 2025)
Irritant contact dermatitis (ICD) is a non-immunologic inflammatory skin disorder resulting from direct damage to the epidermal barrier by chemical, physical, or biological agents. ICD is more common than allergic contact dermatitis since most individuals are at risk of repeated exposure to irritants in daily activities, such as detergents. We report the case of a 54-year-old woman presenting with peeling, erythema, pruritus, and stinging pain on both hands after washing clothes with powdered detergent without protective gloves. Dermatologic examination revealed erythematous plaques with thick scales, diffuse borders, and fissures on the dorsal and palmar regions bilaterally. The diagnosis of ICD was established based on a clear exposure history, characteristic clinical features, and the absence of allergic manifestations. Management included ceramide-based moisturizer to restore skin barrier function, high-potency topical corticosteroid (clobetasol propionate 0.05%) to reduce inflammation, and oral antihistamine (cetirizine) to relieve pruritus. Patient education emphasized adherence to therapy, skin hygiene, and strict avoidance of repeated detergent exposure. Marked clinical improvement was achieved within a short period following combination therapy. This case highlights detergent exposure as an important cause of ICD among housewives and underscores the significance of preventive strategies, including the use of personal protective equipment, safer cleaning alternatives, and continuous patient education. Early recognition and comprehensive management are essential to reduce recurrence and improve patient quality of life.